TRAINING ON DEVELOPING TEACHING MATERIALS FOR ELEMENTARY SCHOOLS USING CANVA - Frijuniarsi, Nurul; Astuti, Natalia Tri (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2024)
This community service activity aims to improve the skills of partners, namely teachers at SDI ASIH AULADI, in creating interesting and of course targeted teaching aids. This is deemed necessary to improve teachers' skills in preparing interactive teaching materials, which are certainly useful in the teaching and learning process. Several techniques, such as surveys, observations, and interviews, were used to gather information about the needs and problems of partners. This activity lasted for one day and lasted for six hours. The implementing team conducted teaching followed by direct assistance regarding the steps to create simple teaching materials using Canva. The results were quite satisfying, where the participants had new knowledge and skills in increasing their creativity by creating interesting and innovative teaching materials.